Karakteristik Ibu berhubungan dengan Pemberian ASI Eksklusif pada Bayi usia 0-6 bulan di Desa Kamal Kabupaten Seram Bagian Barat - Zasendy Rehena (MOLUCCAS HEALTH JOURNAL, 2021)
Breast milk is the only food that is best for babies, because it has the most complete nutritional composition, exclusive breastfeeding is highly recommended. Exclusive breastfeeding is breastfeeding for 6 months without other additional food from birth until the baby is 6 months old. Many factors affect exclusive breastfeeding, one of which is the mother's characteristics, such as age, education, occupation and knowledge of the mother. The purpose of this study was to determine the relationship between maternal characteristics and exclusive breastfeeding for infants aged 0-6 months in Kamal Village, West Seram Regency. Methods This research uses descriptive research using a cross sectional design. Sampling with total sampling method. The data were analyzed by using the chi square test. The results showed that the mother's characteristics consisting of age, education and mother's knowledge were not related to exclusive breastfeeding for infants aged 0-6 months in Kamal Village with a value of > 0.05. Occupational variables related to exclusive breastfeeding with p value = 0.020 < 0.05. The conclusion is that the mother's age, education and knowledge are not related, while work is related to exclusive breastfeeding for infants aged 0-6 months in Kamal Village. Suggestions to health workers to increase mother's knowledge about the benefits of exclusive breastfeeding through counseling.Keywords: age, education, occupation, knowledge, exclusive breastfeeding